Լեզվի հիմնահարցը հայկական ինքնության արդիականացման լուսավորական նախագծում - Նանե Մովսիսյան (ՀՀ ԳԱԱ հրատ.)
В статье обсуждается проблема языка в период армянского просветительства, переход от грабара к ашхарабару. В частности, выдвигаются два противоречащих друг другу мнения по поводу перехода от грабара к ашхарабару, аргументы и контраргументы.The article discusses the issue of the language, particularly, the transition from literal to modern Armenian during the Armenian Enlightenment. Two contradictory views, arguments and counterarguments to the transition from literal to modern Armenian are put forward.
Keywords: Philosophy; Philology; Linguistics